Formation Mechanisms and Control Methods of Cyanobacteria Bloom - Yang, Xuebin (Transactions on Environment, Energy and Earth Sciences, 2024)
Water, a vital resource of human, has been contaminated to an unprecedented extent worldwide. The formation mechanisms and control methods of cyanobacteria bloom have raised several serious concerns globally due to their significant implications for aquatic life, water environment, and public health. This paper explores causes, forming mechanisms, and control methods of cyanobacteria blooms in the context of biological water pollution. Identifying different types of pollution and forms of pollutant is crucial for determining the most suitable solution. Various factors influence the growth of cyanobacteria blooms, including natural processes and human activities. The formation process requires the convergence of different factors. Scientists implement targeted control methods to thwart the growth of cyanobacteria bloom based on the stage of the growth and environmental conditions. Future research needs to focus on developing new measures to address cyanobacteria blooms and conceptualizing the complex systems professionally. This paper concludes the current findings on cyanobacteria blooms, drawing attention towards further research on cyanobacteria bloom.